Strategi Pengajaran “Berbicara (Speaking)” Bahasa Inggris pada Siswa SMA - Wulan Yulian Anggini; Mulyadi Mulyadi (Peneliti.net, 2020)
The ability to speak English among students in Indonesia is very minimal, even though students in Indonesia have studied English since Kindergarten to High School. This raises the question, why did this happen? This study aims to describe the English teaching strategies used by teachers to improve students' speaking skills at school. The sample of this research is the students of class XII SMA Cibinong, West Java, using qualitative methods. Researcher interviews teachers and students in the process of learning English. From this study it was found that the teacher's social strategy is very important because it can make students accustomed to speak English in daily life. Students are not only speak English during English lesson, but they can also speak English whenever needed. The implementation of the social strategy by the teacher for class XII students has been implemented quite well and successful. Then the results of this study also show that students who have the best scores in English lesson use other strategies that encourage themselves to be more proficient in speaking English.